2019
DOI: 10.1111/iju.14088
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the influence of transrectal and transperineal prostate biopsies on erectile function: A prospective observational single‐center study

Abstract: Objectives To assess the impact of transrectal versus transperineal prostate biopsy on erectile function. Methods This was a single‐center, observational, prospective study of consecutive patients who underwent a prostate biopsy (transrectal or transperineal/fusion biopsy). Study participants completed the International Index of Erectile Function‐5 questionnaire before the procedure, and 3 and 6 months after. Prostatic biopsies were carried out following the standard procedure for both techniques. Results The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
1
6
1
Order By: Relevance
“…In contrast, the current study discovered that TRUS-guided PB had no significant effect on erectile function. Similarly, in a study by García Rojo et al, there were no significant differences between pre-biopsy and post-biopsy IEEF-5 scores at 3 and 6 months, and neither the number of biopsy cores nor the number of previous biopsies influenced IEEF-5 scores [18]. The majority of studies, however, suggest that TRUS-guided PB only has a temporary impact on erectile function [19][20][21].…”
Section: Discussionmentioning
confidence: 90%
“…In contrast, the current study discovered that TRUS-guided PB had no significant effect on erectile function. Similarly, in a study by García Rojo et al, there were no significant differences between pre-biopsy and post-biopsy IEEF-5 scores at 3 and 6 months, and neither the number of biopsy cores nor the number of previous biopsies influenced IEEF-5 scores [18]. The majority of studies, however, suggest that TRUS-guided PB only has a temporary impact on erectile function [19][20][21].…”
Section: Discussionmentioning
confidence: 90%
“…4 In the present study, although no data were collected until 1 month after the biopsies, the PBs had no influence on erectile function. 5 In addition, there was no significant difference in erectile function between the transrectal and transperineal approaches at 3 and 6 months. 5 This information would be a factor in deciding the best approach to PB for patients.…”
Section: Editorial Commentmentioning
confidence: 83%
“…5 In addition, there was no significant difference in erectile function between the transrectal and transperineal approaches at 3 and 6 months. 5 This information would be a factor in deciding the best approach to PB for patients.…”
Section: Editorial Commentmentioning
confidence: 83%
“…24 In addition, Garcia et al showed that TTP biopsy does not impact on erectile function compared to TR biopsy at least in the medium term up to six months. 27 Another possible explanation is that the higher median age in the transperineal group contributed to the findings. However, there was only a small age difference, and the biopsy group remained a predictor of EFR on multivariate analysis accounting for age.…”
Section: Discussionmentioning
confidence: 95%